PENDIDIKAN TOLERANSI BERAGAMA UNTUK HUMANISME ISLAM DI INDONESIA - Said, Nur (Program Studi Pendidikan Agama Islam, 2017)
RELIGIOUS TOLERANCE EDUCATION FOR ISLAMIC HUMANISM IN INDONESIA. This paper is organized as a response to the turmoil of religious conflicts in recent years in Indonesia. Islamic educational institution has the responsibility for the actual history of Islam so this nation can be a tolerant or intolerant nation. This study focused on: (1) Rediscovering Islamic educational orientation in Indonesia; (2) Analysing the causes of Islamic education in the perspective of theological insight of religious tolerance; (3) Offering the core values in Islamic education that are relevant for the development of Islamic humanism education in Indonesia. The research used philosophical and historical approaches because it involved a critical study and Islamic intellectual history in Indonesia. The findings were that Islamic education needs to put the religious humanism as core values in its main orientation. While the education problems related to its goals, contents, methods and evaluation showed that the tendency highlighting aspects of sectoral-fiqhiyah was more than robbaniyyah universal aspect. It is necessary to have reorientation of Islamic education which take priority on morals including moral values of religious tolerance over fiqh like the treatises message of Prophet as a complement of humanism morals in people's lives.